2002
DOI: 10.1017/s1355838202020046
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the essential mRNA export factor Yra1p is autoregulated by a splicing-dependent mechanism

Abstract: Recent evidence supports the idea that pre-mRNA splicing and mRNA export are mechanistically coupled. In metazoans, this process appears to be mediated by a multicomponent complex, which associates with the spliced RNA upstream of the exon-exon junction. One of these components (Aly/REF) has a homolog in the budding yeast Saccharomyces cerevisiae known as Yra1p. The YRA1 gene is essential for growth and required for mRNA export. Notably, YRA1 is one of the only ;5% intron-containing genes in yeast. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 40 publications
(31 reference statements)
6
64
0
Order By: Relevance
“…Additionally, some of our predictions were previously reported as alternative 39ss (Davis et al 2000;Yassour et al 2009;Gahura et al 2011), which adds support to our proposed model, where premRNA secondary structure aids 39ss selection. Nonetheless, most of the splicing variation reported so far in yeast (Davis et al 2000;Preker et al 2002;Juneau et al 2007Juneau et al , 2009Pleiss et al 2007;Yassour et al 2009;Bergkessel et al 2011;Hossain et al 2011) corresponds to intron retention events and not to alternative 39ss selection and, hence, could not be recapitulated using our model. Using various yeast strains and conditions, we are able to experimentally validate a number of candidate alternative 39ss, further supporting our predictive model and confirming the existence of alternative 39ss selection in yeast.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, some of our predictions were previously reported as alternative 39ss (Davis et al 2000;Yassour et al 2009;Gahura et al 2011), which adds support to our proposed model, where premRNA secondary structure aids 39ss selection. Nonetheless, most of the splicing variation reported so far in yeast (Davis et al 2000;Preker et al 2002;Juneau et al 2007Juneau et al , 2009Pleiss et al 2007;Yassour et al 2009;Bergkessel et al 2011;Hossain et al 2011) corresponds to intron retention events and not to alternative 39ss selection and, hence, could not be recapitulated using our model. Using various yeast strains and conditions, we are able to experimentally validate a number of candidate alternative 39ss, further supporting our predictive model and confirming the existence of alternative 39ss selection in yeast.…”
Section: Discussionmentioning
confidence: 92%
“…S3). To the best of our knowledge, these two cases of alternative splicing have not been reported before in previous analyses of splicing variation in yeast (Davis et al 2000;Preker et al 2002;Juneau et al 2007Juneau et al , 2009Pleiss et al 2007;Yassour et al 2009;Bergkessel et al 2011;Hossain et al 2011). Some of the negative cases were shown before to have splicing variation different from alternative 39ss selection: HMF1 and REC102 Each predicted AG is given as the intron coordinates (chromosome, start, end, strand), the gene name, and the distance to the BS (calculated as explained in Materials and Methods).…”
Section: Validation Of Predicted Alternative 39ssmentioning
confidence: 85%
“…Indeed, introns have been shown to increase the fitness of yeast in two ways: (1) regulated splicing posttranscriptionally regulates gene expression (Engebrecht et al 1991;Li et al 1996;Nakagawa and Ogawa 1999;Preker et al 2002;Juneau et al 2007;Parenteau et al 2008) and (2) introns can function to enhance the transcriptional and translational output of the genes they occupy ( Juneau et al 2006). Here we provide compelling evidence that introns also improve the fitness of yeast by increasing protein diversity through alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, all 13 meiosis-specific introncontaining genes are regulated post-transcriptionally with splicing repressed during vegetative growth and induced during sporulation (Engebrecht et al 1991;Nakagawa and Ogawa 1999;Juneau et al 2007). Other examples of regulated splicing include YRA1 and MTR2 (RNA export) (Preker et al 2002;Parenteau et al 2008) and RPL30 (ribosomal) (Li et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Yra1p was originally isolated in a screen for yeast genes that cause overexpressionmediated growth arrest (Espinet et al 1995), and was also shown to possess RNA-RNA annealing activity (Portman et al 1997). The level of Yra1p is tightly regulated by a negative feedback mechanism that involves splicing of its unusual intron (Preker et al 2002). Depletion of Yra1p results in nuclear accumulation of poly(A) + RNA, supporting its direct role in mRNA export in yeast (Strasser and Hurt 2000;Stutz et al 2000).…”
Section: Introductionmentioning
confidence: 95%